RAP-PCR fingerprinting reveals time-dependent expression of development-related genes following differentiation process of Bacillus thuringiensis - Huang, Tianpei; Yu, Xiaomin; Gelbič, Ivan; Guan, Xiong (Canadian journal of microbiology, 2015)
Gene expression profiles are important data to reveal the functions of genes putatively involved in crucial biological processes. RNA arbitrarily primed polymerase chain reaction (RAP-PCR) and specifically primed reverse transcription polymerase chain reaction (RT-PCR) were combined to screen differentially expressed genes following development of a commercial Bacillus thuringiensis subsp. kurstaki strain 8010 (serotype 3a3b). Six differentially expressed transcripts (RAP1 to RAP6) were obtained. RAP1 encoded a putative triple helix repeat-containing collagen or an exosporium protein H related to spore pathogenicity. RAP2 was homologous to a ClpX protease and an ATP-dependent protease La (LonB), which likely acted as virulence factors. RAP3 was homologous to a beta subunit of propionyl-CoA carboxylase required for the development of Myxococcus xanthus. RAP4 had homology to a quinone oxidoreductase involved in electron transport and ATP formation. RAP5 showed significant homology to a uridine kinase that mediates phosphorylation of uridine and azauridine. RAP6 shared high sequence identity with 3-methyl-2-oxobutanoate-hydroxymethyltransferase (also known as ketopantoate hydroxymethyltransferase or PanB) involved in the operation of the tricarboxylic acid cycle. The findings described here would help to elucidate the molecular mechanisms underlying the differentiation process of B. thuringiensis and unravel novel pathogenic genes.
Keywords: bakteriální proteiny; regulace genové exprese u bakterií; Bacterial Proteins; Gene Expression Regulation, Bacterial; Spores, Bacterial; Bacillus thuringiensis; Reverse Transcriptase Polymerase Chain Reaction; vývojová regulace genové exprese; spory bakteriální; Gene Expression Regulation, Developmental; polymerázová řetězová reakce s reverzní transkripcí; DNA fingerprinting; DNA Fingerprinting